2013
DOI: 10.1002/clen.201200408
|View full text |Cite
|
Sign up to set email alerts
|

Mass Balance Study on Phosphorus Removal in Constructed Wetland Microcosms Treating Polluted River Water

Abstract: A number of studies have showed that the mass removal rates of phosphorus (P) in different constructed wetlands (CWs) varied significantly, and it is essential to quantify the contributions of major P removal processes in order to improve system design. The objective of this study was to investigate the effects of vegetation, hydraulic retention time (HRT), and water temperature on P removal from polluted river water and to quantify the contributions of different P removal pathways in surface CWs. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 28 publications
4
31
0
4
Order By: Relevance
“…The results indicate that during the process of artificial wetlands removing P-pollutants, phosphorus removed by other means like substrates and microorganisms cover most proportion of wetlands removing phosphorus. Similar to researches of many scholars, Gagnon V et al [8] verified that Ppollutants are mainly distributed in substrates and wetland system with plants has higher efficiency in removing total phosphorus; Chung A K C et al [9] figured out that removal rate of total phosphorus by artificial wetlands is 52 while Paccumulation in plant body is not 5% enough; Wu H et al [10] also believed that efficiency of artificial wetlands removing P-pollutants is 67% and maximum P-removing efficiency of plants reaches 34.17%. All of which may be related to multiple factors like different plants and substrate types and different pollutant concentrations, Konnerup D et al [11] found that the lower content of total phosphorus in sewage is, the more obvious the P-removing effect by artificial wetlands will be.…”
Section: Resultsmentioning
confidence: 59%
“…The results indicate that during the process of artificial wetlands removing P-pollutants, phosphorus removed by other means like substrates and microorganisms cover most proportion of wetlands removing phosphorus. Similar to researches of many scholars, Gagnon V et al [8] verified that Ppollutants are mainly distributed in substrates and wetland system with plants has higher efficiency in removing total phosphorus; Chung A K C et al [9] figured out that removal rate of total phosphorus by artificial wetlands is 52 while Paccumulation in plant body is not 5% enough; Wu H et al [10] also believed that efficiency of artificial wetlands removing P-pollutants is 67% and maximum P-removing efficiency of plants reaches 34.17%. All of which may be related to multiple factors like different plants and substrate types and different pollutant concentrations, Konnerup D et al [11] found that the lower content of total phosphorus in sewage is, the more obvious the P-removing effect by artificial wetlands will be.…”
Section: Resultsmentioning
confidence: 59%
“…We used a mass balance method [8,11,12] in this study to calculate P balance of the watershed which was regarded as a whole in this study and the lake itself in one year (2010). The watershed boundary is the natural catchment area, not including the watershed form where water is channeled.…”
Section: Methodsmentioning
confidence: 99%
“…It contained: the amounts of nitrogen imported and exported from the microcosm systems; the amounts of nitrogen assimilated by plants; the amounts of nitrogen absorbed by the substrate; other losses, including ammonia volatilization, N2O and N2 emission [19]. The calculative pattern for the nitrogen mass balance is shown below [20]:…”
Section: Nitrogen Analysismentioning
confidence: 99%